2019
DOI: 10.3389/fphar.2019.00459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) for Poorly Water-Soluble Talinolol: Preparation, in vitro and in vivo Assessment

Abstract: Objective The aim of this study was to investigate the in vitro and in vivo performance of self-nanoemulsifying drug delivery systems (SNEDDSs) of talinolol (TAL), a poorly water-soluble drug. Methods Self-nanoemulsifying drug delivery systems of TAL were prepared using various oils, non-ionic surfactants and/or water-soluble co-solvents and assessed visually/by droplet size measurement. Equilibrium solubility of TAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 38 publications
2
65
0
1
Order By: Relevance
“…The anhydrous SNEDDS samples were visually evaluated for homogeneity and appearance. As a preliminary screening, drug-free SNEDDS formulations were mixed with deionized water at 1:100 w/w ratio to provide fast evaluation of formulation appearance, homogeneity and spontaneity upon aqueous dilution [62][63][64]. Furthermore, SNEDDS formulations were loaded with CUR and PP at ≈80% of their equilibrium solubility and were then subjected to 1:1000 w/w aqueous dilution prior to formulation evaluation.…”
Section: Appearance and Morphologymentioning
confidence: 99%
“…The anhydrous SNEDDS samples were visually evaluated for homogeneity and appearance. As a preliminary screening, drug-free SNEDDS formulations were mixed with deionized water at 1:100 w/w ratio to provide fast evaluation of formulation appearance, homogeneity and spontaneity upon aqueous dilution [62][63][64]. Furthermore, SNEDDS formulations were loaded with CUR and PP at ≈80% of their equilibrium solubility and were then subjected to 1:1000 w/w aqueous dilution prior to formulation evaluation.…”
Section: Appearance and Morphologymentioning
confidence: 99%
“…Similar results were reported by Kazi et al where droplet size was found to be around 150 nm having spherical shape. 27 Another crucial parameter is polydispersity index (PDI), which reflected positively on formulation physical stability. Our results were less than 0.5 which indicates uniformity of droplet size distribution of limonene within the formulation and affirms its homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The interfacial tension between the lipophilic and hydrophobic components of SEDDSs are reduced by surfactants. They create an interfacial film between the two immiscible phases for the purpose of generating a dispersion [3][4][5][6][7][8]72]. During formulation of SEDDSs, higher emulsification properties are achieved by including surfactants with HLB values exceeding a value of 12.…”
Section: Surfactantsmentioning
confidence: 99%
“…Self-emulsifying drug delivery systems (SEDDSs) are isotropic blends of an active compound with a mixture of lipids, surfactants, and co-surfactants that produce spontaneous oil-in-water emulsions (dispersions) during moderate agitation in an aqueous phase, such as the upper gastrointestinal tract. A highly solubilised, thermodynamically stable phase of drug for improved drug absorption is subsequently formed [3][4][5][6][7][8]. SEDDS, however, is a comprehensive term for selected lipid-based drug delivery systems and can rather be differentiated into three categories in terms of droplet size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation